PUBLIC PERCEPTION OF IMMIGRATION CONTENT ON SOCIAL MEDIA INSTAGRAM AT THE TPI EAST JAKARTA CLASS I IMMIGRATION OFFICE - Muhammad Aditya Majdi (TEMATICS: Technology ManagemenT and Informatics Research Journals, 2019)
Public perception of immigration content at the TPI East Jakarta Class I Immigration Office is very important in determining the quality of information and understanding of immigration provided to the public by focusing on social media Instagram. With some literacy regarding public perceptions it can produce a public view of immigration content that has been disseminated through social media Instagram TPI Class I Immigration Office, East Jakarta. This can be used as study and learning material in seeing some of the shortcomings that must be addressed by the TPI East Jakarta Class I Immigration Office regarding public perceptions of immigration content. With the descriptive qualitative research method, it explains that there are still gaps or shortcomings of immigration content disseminated through social media Instagram TPI Class I Immigration Office, East Jakarta. So it is very necessary to make several further research studies related to public perceptions of immigration content so as to harmonize understanding between the information provider and the recipient of the information.